Issues in Christian-Muslim relations: a Malaysian Christian perspective - Walters, Albert Sundararaj (Islam and Christian-Muslim relations, 2007)
Malaysia is a democratic secular federation with Islam as its official religion. Over the last few decades, this unique model of tolerance and accommodation has been undergoing astounding developments politically, socially and economically. Intense intra-Muslim struggles coupled with increased state-mobilized Islamizing efforts have produced disturbing knock-on effects on non-Muslim minorities. Religion is so profoundly interwoven with race, ethnicity, politics and economics that it is impossible to speak of one without touching upon the others. This article aims to elucidate key practical issues affecting Christians living in a majority Islamic context. It further proposes significant policy options for managing Muslim–Christian relations in twenty-first-century Malaysia. Education is crucial for promoting interreligious harmony, religious freedom, and respect for people of different traditions. More collaborative endeavours through interfaith dialogue should help Malaysians transcend cultural, racial, linguistic and religious barriers. Both Christian and Muslim faith communities need to learn more about and from each other and to move forward towards nation-building and a common destiny.